Detecting AGG Interruptions in Male and Female FMR1 Premutation Carriers by Single‐Molecule Sequencing. Issue 3 (17th January 2017) - Ardui, Simon; Race, Valerie; Zablotskaya, Alena; Hestand, Matthew S.; Van Esch, Hilde; Devriendt, Koenraad; Matthijs, Gert; Vermeesch, Joris R.
Abstract : Single‐Molecule Sequencing enables the detection of AGG units interrupting the CGG repeat of the FMRl gene not only in males, but also in females. This knowledge is of great value to determine the risk a female with an FMRl premutation (55–200 repeat units) will transmit a full mutation (>200 repeat units) to her offspring. ABSTRACT: The FMR1 gene contains an unstable CGG repeat in its 5′ untranslated region. Premutation alleles range between 55 and 200 repeat units and confer a risk for developing fragile X‐associated tremor/ataxia syndrome or fragile X‐associated primary ovarian insufficiency. Furthermore, the premutation allele often expands to a full mutation during female germline transmission giving rise to the fragile X syndrome. The risk for a premutation to expand depends mainly on the number of CGG units and the presence of AGG interruptions in the CGG repeat. Unfortunately, the detection of AGG interruptions is hampered by technical difficulties. Here, we demonstrate that single‐molecule sequencing enables the determination of not only the repeat size, but also the complete repeat sequence including AGG interruptions in male and female alleles with repeats ranging from 45 to 100 CGG units. We envision this method will facilitate research and diagnostic analysis of the FMR1 repeat expansion.